Severe symptom reporting in surgical patients assessed through an EHR-integrated ePRO questionnaire at 6 cancer centers. Issue 28 (1st October 2022) - Wong, Sandra L.; Hazard-Jenkins, Hannah W.; Schrag, Deborah; Osarogiagbon, Raymond U.; Dizon, Don S.; Bian, Jessica J; Cronin, Christine; Tramontano, Angela; Hassett, Michael J.
Abstract : 243 Background: Patients (pts) undergoing surgery for suspected malignancy may experience burdensome post-operative symptoms which can compromise outcomes and necessitate acute care. In prior randomized controlled trials at academic medical centers, patient-reported outcome (PRO)-based symptom management solutions improved clinical outcomes. Attempts to generalize this approach to real-world surgical pts have been challenged by perceptions that severe symptoms rarely occur, responding to severe symptoms can be burdensome, and uncertainty about which symptoms are likely to be severe and need interventions. Methods: Six US-based healthcare systems deployed eSyM, an EHR-integrated symptom management program. Pts undergoing surgery for suspected or confirmed thoracic (THOR), gastrointestinal (GI), and gynecologic (GYN) malignancies received automated questionnaires via MyChart portal 1-3 times weekly for up to 3 months after discharge. Questionnaires based on the PRO-CTCAE included 10 required and 20 optional symptoms, all scored as 0 (no symptoms), 1 (mild), 2 (moderate), or 3 (severe). Additional questions assessed functional status, overall wellbeing, wound discharge, and wound redness. Frequency and predictors of severe reporting were assessed using descriptive statistics and logistic regression modeling. Results: 21, 012 surgical eSyM questionnaires were submitted between October 2019 - March 2022 by 3, 781 unique pts (median age 63 years, 66.9% female, 92.1% white, 57.9% married, and 37.5% retired). 17% of questionnaires (16% of GI, 14% of GYN, and 21% of THOR) included at least 1 severe symptom. Frequencies of severe symptom reporting appear in Table with physical function impairment, general pain, and fatigue as the top three. Severe symptoms were more likely to be reported by younger, female, or unemployed pts(p < 0.01). In comparison to GI pts, GYN pts reported fewer and THOR pts reported more severe symptoms (p < 0.03). Conclusions: A meaningful minority of pts reported severe symptoms, suggesting that symptom monitoring could benefit pts without over-taxing clinicians. There were few strong patient-level predictors of severe symptoms, arguing that population surveillance may be preferable to targeted surveillance. Interventions are needed to address common severe symptoms and future studies should define most effective mitigation strategies for these symptoms. Clinical trial information: NCT03850912. Top severe symptoms reported by surgical pts. Score 0 (no symptoms) Score 1 (mild) Score 2 (moderate) Score 3 (severe) Symptoms # Responses % % % % Physical function 20, 695 30.3 40.5 16.7 12.5 General pain 20, 392 29.7 40.2 19.6 10.5 Fatigue 18, 287 24.5 48.3 20.6 6.6 Overall wellbeing 20, 680 28.8 45.4 20.1 5.6 Constipation 20, 780 64.7 20.7 11 3.6 Anxiety 17, 578 57.1 29.2 10.8 2.9 Wound discharge 20, 297 90 n/a 10 n/a Wound redness 20, 305 85.9 n/a 14.1 n/a